New Insights into the Provision of Health Services in Indonesia : A Health Workforce Study - Rokx, Claudia; Giles, John; Satriawan, Elan; Marzoeki, Puti; Harimurti, Pandu; Yavuz, Elif (World Bank, 2012)
Indonesia has made improving the access to health workers, especially in rural areas, and improving the quality of health provider's key priority areas of its next five-year development plan. Significant steps and policy changes were taken to improve the distribution of the health workforce, in particular the contracted doctors program and later the contracted midwives program, but few studies have been undertaken to measure the actual impact of these policies and programs. This book is part of the inputs prepared at the request of the government of Indonesia's national development agency, Bappenas, to inform the development of the next national development plan 2010-14. Other inputs include reports on health financing, fiscal space for health, health public expenditure review, and assessments of maternal health and pharmaceuticals. Study findings highlight the importance not only of improving the supply of health care, but also of improving quality, so as to improve health outcomes. Over the period studied, important gains in the determinants of health outcomes have occurred in Indonesia. At the same time, however, the study shows that Indonesia, despite the significant gains, continues to suffer from serious challenges in the number and distribution, and in particular the quality, of its health workers.